Longitudinal Risk of Adverse Events in Patients With Acute Kidney Injury After Percutaneous Coronary Intervention: Insights From the National Cardiovascular Data Registry. (April 2017) - Valle, Javier A.; McCoy, Lisa A.; Maddox, Thomas M.; Rumsfeld, John S.; Ho, P. Michael; Casserly, Ivan P.; Nallamothu, Brahmajee K.; Roe, Matthew T.; Tsai, Thomas T.; Messenger, John C.
Abstract : Background—: Acute kidney injury (AKI) remains a common complication after percutaneous coronary intervention (PCI) and is associated with adverse in-hospital patient outcomes. The incidence of adverse events after hospital discharge in patients having post-PCI AKI is poorly defined, and the relationship between AKI and outcomes after hospital discharge remains understudied. Methods and Results—: Using the National Cardiovascular Data Registry CathPCI registry, we assessed the incidence of AKI among Medicare beneficiaries after PCI from 2004 to 2009 and subsequent post-discharge adverse events at 1 year. AKI was defined using Acute Kidney Injury Network (AKIN) criteria. Adverse events included death, myocardial infarction, bleeding, and recurrent kidney injury. Using Cox methods, we determined the relationship between in-hospital AKI and risk of post-discharge adverse events by AKIN stage. In a cohort of 453 475 elderly patients undergoing PCI, 39 850 developed AKI (8.8% overall; AKIN stage 1, 85.8%; AKIN 2/3, 14.2%). Compared with no AKI, in-hospital AKI was associated with higher post-discharge hazard of death, myocardial infarction, or bleeding (AKIN 1: hazard ratio [HR], 1.53; confidence interval [CI], 1.49–1.56 and AKIN 2/3: HR, 2.13; CI, 2.01–2.26), recurrent AKI (AKIN 1: HR, 1.70; CI, 1.64–1.76; AKIN 2/3: HR, 2.22; CI, 2.04–2.41), and AKI requiring dialysis (AKIN 1: HR, 2.59; CI, 2.29–2.92; AKIN 2/3: HR, 4.73; CI, 3.73–5.99). For each outcome, the highest incidence was within 30 days. Conclusions—: Post-PCI AKI is associated with increased risk of death, myocardial infarction, bleeding, and recurrent renal injury after discharge. Post-PCI AKI should be recognized as a significant risk factor not only for in-hospital adverse events but also after hospital discharge. Abstract : Supplemental Digital Content is available in the text.